2022
DOI: 10.1097/icl.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanics and Intraocular Pressure Following Scleral Lens Wear in Penetrating Keratoplasty and Keratoconus

Abstract: Objective:To compare corneal biomechanics and intraocular pressure (IOP) in keratoconus and penetrating keratoplasty eyes before and after nonfenestrated scleral lens wear.Methods:Twenty-three participants were enrolled, and 37 eyes were included in the analysis (11 penetrating keratoplasty and 26 keratoconus). A range of corneal biomechanical parameters and IOP were measured using the CORVIS ST before and after 8 hr of nonfenestrated scleral lens wear (Keracare, Acculens, Denver, CO).Results:Before lens wear,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Despite that, a previous study did not found any changes on IOP or corneal biomechanics (measured with Corvis ST) after 8 h of SL wear in patients with keratoplasty. [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that, a previous study did not found any changes on IOP or corneal biomechanics (measured with Corvis ST) after 8 h of SL wear in patients with keratoplasty. [25].…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated the influence of soft contact lens wear on corneal biomechanics and found a tendency for higher CRF values on myopic contact lens wearers whereas CH did not show a clear trend of change, suggesting that there may be some alterations on corneal microstructure and physiology following chronic CL wear (which may affect viscoelasticity). [24] In the same line, a study by Mukesh et al [25] aimed to evaluate the influence of SL wear on corneal biomechanics and IOP in patients with keratoconus and penetrating keratoplasty. In contrast with the results of the previous study in myopic contact lens wearers, the authors did not find significant changes in the outcomes in both groups.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term use may also cause corneal warpage or remodeling, leading to increased corneal surface asymmetry and irregularity. On the other hand, scleral lenses, due to their large size and rigid design, can potentially cause hypoxia and physiological changes in the cornea and underlying tissues [ 62 , 63 ]. The lens-cornea clearance, along with lens fitting and wearing time, may induce stress and potential changes to the corneal structure.…”
Section: Factors Leading To Alterations Of Biomechanical Propertiesmentioning
confidence: 99%
“…IOP returned to baseline levels after the lenses were removed, indicating that the IOP increase was temporary. Kumar et al (2022) studied the changes in corneal biomechanics and IOP in 37 eyes with keratoconus and post-PK, after ScL wear. Scleral contact lenses with center thickness (250) μm, DK (100), and diameters (15.90-16.00) mm were fitted.…”
Section: Intraocular Pressure Variation With Scleral Lensesmentioning
confidence: 99%